2015
DOI: 10.1186/s13568-015-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Surfactin yield by improving the medium composition and fermentation process

Abstract: Surfactin is one of the most promising biosurfactants due to its extraordinary surface activity. Commonly, the well-established Cooper medium, a glucose-based mineral salt medium, is utilized for the microbial production of Surfactin. The current study investigated the enhancement of Surfactin yields by analyzing the effects of different glucose concentrations, next to the introduction of an alternative chelating agent and nitrogen source. The utilization of 8 g/L glucose, 0.008 mM Na3citrate and 50 mM (NH4)2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 24 publications
4
42
0
1
Order By: Relevance
“…Besides that, foam resulting from emulsification of biosurfactants due to vigorous agitation during cultivation might decrease the transfer efficiency of oxygen into the liquid medium [ 17 ] in which countermeasures can be taken to eliminate foaming but will further drive-up the production cost. To overcome these problems, various researchers were looking into cheaper alternative substrates, optimization of the environmental conditions, and improvement on the downstream recovery processes [ 18 , 19 , 20 , 21 ]. Still, no definitive method could contribute to the overall cost saving for biosurfactant production.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, foam resulting from emulsification of biosurfactants due to vigorous agitation during cultivation might decrease the transfer efficiency of oxygen into the liquid medium [ 17 ] in which countermeasures can be taken to eliminate foaming but will further drive-up the production cost. To overcome these problems, various researchers were looking into cheaper alternative substrates, optimization of the environmental conditions, and improvement on the downstream recovery processes [ 18 , 19 , 20 , 21 ]. Still, no definitive method could contribute to the overall cost saving for biosurfactant production.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies concerning free cells production of lipopeptides have been reported. Several parameters such as carbon sources, nitrogen sources, and temperature were studied [ 11 , 12 ]. In addition, the production of biosurfactants by immobilized cells of Bacillus subtilis was well studied [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that simple cultivation integrated foam fractionation is an effective tool for biosurfactant production e.g. of surfactin using Bacillus subtilis (Chen et al 2006 ; Willenbacher et al 2014 , 2015 ) or HFBII using Saccharomyces cerevisiae (Winterburn et al 2011 ). The usability of foam fractionation in rhamnolipid purification and concentration in a cell free process was shown previously (Sarachat et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%